Transient radiative transfer in variable index media using the discrete transfer method. (November 2020) - Dehghanian, A.; Sarvari, S.M. Hosseini
Highlights: The transient radiative transfer in variable index media is solved by the discrete transfer method. The solution method is applicable for continuous or non-continuous refractive index distributions. The method is adopted for one- and multi-dimensional media. The boundaries may be exposed to collimated irradiation. The reflectance and transmittance are reported for one- and two-dimensional media. Abstract: The discrete transfer method is adopted to solve the transient radiative transfer with collimated or diffuse irradiation in variable index media with arbitrary distribution of refractive index. The advantage of this approach is its ability to simulate the transient radiation in semi-transparent media with non-continuous refractive index distributions. The solution method is verified by comparison the results with those reported in literature for one, two and three-dimensional cases. The reflectance and transmittance for some locations over the boundaries are obtained, and the effects of optical thickness, scattering albedo, and scattering phase function are examined.